Pendekatan Sosiologis terhadap Penolakan Pornografi - Fahmi, Muhammad; Hasibuan, Edi Saputra (AL-SULTHANIYAH, 2026)
This study examines the rejection of pornography in Indonesia by exploring the Islamic legal, social, and moral dimensions that shape public perception. Pornography is regarded as a form of moral deviation that contradicts prevailing religious, cultural, and legal values. The research employs a qualitative descriptive approach by analyzing Islamic normative sources, legal regulations, and societal perspectives concerning the issue of pornography. The findings indicate that the public’s rejection of pornography is grounded in Islamic teachings that emphasize the importance of preserving dignity and morality, supported by the roles of family, education, and media in fostering ethical values. Therefore, the control of pornography in Indonesia requires synergy between legal, moral, and religious approaches to safeguard social integrity and national ethics.